Overexpression of an acidic endo-β-1,3-1,4-glucanase in transgenic maize seed for direct utilization in animal feed. - Yuhong Zhang (Public Library of Science (PLoS), 2013)
Background Incorporation of exogenous glucanase into animal feed is common practice to remove glucan, one of the anti-nutritional factors, for efficient nutrition absorption. The acidic endo-β-1,3-1,4-glucanase (Bgl7A) from Bispora sp. MEY-1 has excellent properties and represents a potential enzyme supplement to animal feed. Methodology/principal findings Here we successfully developed a transgenic maize producing a high level of Bgl7AM (codon modified Bgl7A) by constructing a recombinant vector driven by the embryo-specific promoter ZM-leg1A. Southern and Western blot analysis indicated the stable integration and specific expression of the transgene in maize seeds over four generations. The β-glucanase activity of the transgenic maize seeds reached up to 779,800 U/kg, about 236-fold higher than that of non-transgenic maize. The β-glucanase derived from the transgenic maize seeds had an optimal pH of 4.0 and was stable at pH 1.0-8.0, which is in agreement with the normal environment of digestive tract. Conclusion/significance Our study offers a transgenic maize line that could be directly used in animal feed without any glucanase production, purification and supplementation, consequently simplifying the feed enzyme processing procedure.